Contour current imprints and contourite drifts in the Bahamian archipelago. Issue 4 (25th March 2019) - Mulder, Thierry; Ducassou, Emmanuelle; Hanquiez, Vincent; Principaud, Mélanie; Fauquembergue, Kelly; Tournadour, Elsa; Chabaud, Ludivine; Reijmer, John; Recouvreur, Audrey; Gillet, Hervé; Borgomano, Jean; Schmitt, Anais; et al.
Abstract: New data collected along the slopes of Little and Great Bahama Bank and the abyssal plain of the Bahama Escarpment provides new insights about contour current‐related erosive structures and associated deposits. The Bahamian slope shows abundant evidence of bottom current activity such as furrows, comet‐like structures, sediment waves and drifts. At a seismic scale, large erosion surfaces and main periods of drift growth resulted from current acceleration related to plate tectonic processes and progressive opening and closure of gateways and long‐term palaeoclimate evolution. At present‐day, erosion features and contourite drifts are either related to relatively shallow currents (<1000 m water depth) or to deep currents (>2500 m water depth). It appears that the carbonate nature of the drifts does not impact the drift morphology at the resolution addressed in the present study. Classical drift morphologies defined in siliciclastic environments are found, such as mounded, plastered and separated drifts. In core, contourite sequences show a bi‐gradational trend that resembles classical contourite sequences in siliciclastic deposits showing a direct relationship with a change in current velocity at the sea floor. However, in a carbonate system the peak in grain size is associated with increased winnowing rather than increased sediment supply as in siliciclastic environments. In addition, the carbonate contourite sequence is usually thinner than in siliciclastics because of lower sediment supply rates. Little Bahama Bank and Great Bahama Bank contourites contain open‐ocean input and slope‐derived debris from glacial episodes. Inner platform, platform edge and open ocean pelagic input characterize the classical periplatform ooze during interglacials. In all studied examples, the drift composition depends on the sea floor topography surrounding the drift location and the type of sediment supply. Carbonate particles are derived from either the slope or the platform in slope and toe of slope drifts, very deep contourites have distant siliciclastic sources of sediment supply. The recent discovery of the importance of a large downslope gravitary system along Bahamian slopes suggests frequent interactions between downslope and along‐slope (contour currents) processes. The interlayering of mass flow deposits and contourites at a seismic scale or the presence of surface structures associated with both contour currents and mass flow processes shows that both processes act at the same location. Finally, contour currents have an important impact on the repartition of deep‐water coral mounds. Currents can actively interact with mounds as a nutrient and oxygen supplier or have a passive interaction, with mounds solely being obstacles orienting erosion and deposition.